Islamic Education: origins and methods - Albustanji, Iyad Yousef (Journal of Educational and Psychological Sciences, 2020)
The aim of the research is to stand on the concept of Islamic education as a comprehensive and broad concept that includes all that matters to a person in his life, as it is an independent and integrated educational system characterized by its fixed origins, original curricula, goals, purposes and various methods. The researcher used the method of analytical inductive. This research included several chapters where the first chapter included Islamic education, its definition, its elements and its importance, and the second chapter foundations of Islamic education, while the third chapter talked about the sources of Islamic education The research reached the following results: Attention to Islamic tradition and Islamic culture in all fields in general and the media in particular. And the importance of knowledge and knowledge and its value to man, and the importance of moral values in the stewardship of life. At the end of the research, the eternity of the Creator’s existence was emphasized, and the unseen things that transcend human sense were explained.